TOPOGRAPHY INFLUENCE TOWARDS RAINFALL PATTERN OVER WESTERN JAVA DURING CROSS-EQUATORIAL NORTHERLY SURGE - Qorina Matin, Brilliana
The difference in topography elevation can influence the rainfall patterns on the northern coast of western Java during Cross-Equatorial Northerly Surge (CENS). Previous researchers have suspected a correlation between topography characteristics and the variation in rainfall patterns on Java Island during CENS. However, this correlation has not been thoroughly tested in the previous study. Therefore, further research is needed to understand the mechanisms behind the differences in rainfall patterns due to CENS, which are associated with topographic conditions. To investigate the impact of topography on rainfall patterns in the western Java during CENS, simulations were executed using the Weather Research and Forecasting (WRF) numerical weather prediction model. Three scenarios were used in the simulations: a control simulation with actual topography, a simulation with 50% modification of the topography, and another simulation with 0% modification of the topography. The data used for this research included ERA5 data as input data, Optimum Interpolation Sea Surface Temperature (OISST) data as additional input for updating sea surface temperatures during the simulation period, and Global Multi-resolution Terrain Elevation Data 2010 (GMTED2010) as input data for modifying the topography in the simulations. Based on the simulation results in this study, it can be generally confirmed that after execute the control simulation, the topography scenario simulation with 50% modification, and the topography scenario simulation with 0% modification, there are differences in the rainfall response to CENS in the northern coast and central parts of West Java Island, influenced by the topographic conditions. When the topographic height decreases, the difference between the average rainfall values in the northern coast and central parts of West Java Island also decreases. In the results of the control simulation and the topography scenario simulations 50% and 0% modification, there is a tendency of decreasing average rainfall in a linear along the northern of West Java Island. Based on these findings, it indicates that there is an influence of topography on the rainfall patterns in the western Java.